FORUM MŁODYCH CHIRURGÓWDiagnostics problems of the double primary esophageal cancer – a case report - Wójcik, Norbert; Wójcik, Janusz; Grodzki, Tomasz; Kubisa, Bartosz; Pieróg, Jarosław; Bielewicz, Michał; Wojtyś, Małgorzata (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
A case of 67 year-old woman with solid food dysphagia and recently revealed renal insufficiency is described. Parenteral nutrition as well as pharmacologic treatment of the renal insufficiency resulted in improvement of metabolic status and kidney function parameters. Computed tomography of the thorax with barium contrast examination of the esophagus revealed solitary esophageal infiltration with 4 millimeters stenosis that was seen at the distance of 25 centimeters from the teeth with no signs of mediastinal involvement by the tumor. Gastroscopy and EUS examination was not possible below the stenosis with 2 attempts of taking tissue samples. Bronchoscopy revealed no signs of involvement of the bronchial tree by the tumor. It was decided not to perform EBUS and to operate with intraoperative frozen section. Intraoperatively squamous cell cancer of the esophagus was confirmed and the second cancer of the third lower part of the esophagus with mediastinal infiltration was found surprisingly during surgery. The McKeown esophageal resection had been performed. Postoperative adjuvant radiotherapy was planned, however, the patient died on the tenth postoperative day due to respiratory and circulatory insufficiency as well as recurrent kidney failure. Difficulties with assessment of the esophagus below the stenosis and role of PET in preoperative examination were discussed.